PEER TUTORING STRATEGY TO TEACH READING COMPREHENSION - Sudarsono, Kholifuddin Roma, Y. Gatot Sutapa Y, (Universitas Tanjungpura, 2019)
This study was a quasi-experimental study. It was to find out the use of peer tutoring strategy and its significant effect to teach reading comprehension. The population of this research was the whole year-8 students of SMP NEGERI 2 Pontianak. Cluster random sampling was used to determine the sample. The samples were students of year-8 H as the experimental group and year-8 D as the control group. Measurement technique was employed in this research. The tool of collecting data was reading test and further analyzed by using SPSS software. The research result showed that peer tutoring strategy was effective to teach reading comprehension and Ho rejected since t value > ttable (5.081 > 2.0032). The result of the effect size calculation yielded a strong effect (1.237). In brief, it can be concluded that peer tutoring strategy had the strong effect in teaching reading comprehension of narrative text. It is suggested to be applied in teaching reading comprehension